Diminished angiogenesis in the cornea of mice with heterologous deletion of Connexin 43 gene (Gja1). - Rodrigues, Lucas C. S.; Sinhorini, Idércio L.; Avanzo, José L.; Oloris, Sílvia C. S.; Carneiro, Carolina S.; Lima, Cynthia E.; Fukumasu, Heidge; Costa-Pinto, Frederico A.; Dagli, Maria L. Z. (Brazilian Journal of Veterinary Pathology, 2010)
Angiogenesis is involved in several physiological and pathological processes, and the proliferation of endothelial cells is a central event in the generation of new blood vessels. Gap junctions (GJ) are membrane structures that communicate adjacent cells, contribute to tissue homeostasis, and are important to the control of cell proliferation. Connexins (Cxs) are the proteins that form gap junctions. Endothelial cells may express Cx43, Cx37 and Cx40. In this study, we analyzed the effect of the heterologous deletion of the Gja1 (Cx43 gene) on the development of newly formed blood vessels (NFBV) in the mouse cornea. Heterozygous (Cx43+/-) and wild-type (Cx43+/+) mice were submitted to the silver crystal corneal cauterization model. Two parameters were quantified by image analysis 2 or 6 days after cauterization: NFBV density and length. At days 2 and 6 after corneal cauterization, Cx43+/- mice showed smaller density of NFBV as compared to Cx43+/+ mice. Therefore, deletion of one Gja1 allele (connexin-43 gene) may lead to impaired cell-cell communication in endothelial cells, diminishing angiogenesis after cauterization of the mouse cornea.